Potensi Ekstrak Daun Jati (Tectona grandis L. f.) sebagai Bioherbisida Gulma Teki (Cyperus rotundus L.) dan Gulma Siam (Chromolaena odorata L.) - Siti Nazla Syafaa Kamila; Dyah Weny Respatie; Rani Agustina Wulandari (Vegetalika, 2025)
The presence of Siam weed (Chromolaena odorata L.) and purple nutsedge (Cyperus rotundus L.) in crop fields has been shown to reduce crop quality and productivity. This issue can be mitigated through the use of bioherbicides derived from teak (Tectona grandis Linn. f.) leaf extract, which contains allelochemicals with herbicidal potential. Therefore, this study aimed to quantify the allelopathic compounds in teak leaves and determine the optimal concentrations for controlling the two weed species during germination and early growth. The research was conducted in January-August 2024 at the Crop Production Management Laboratory, Horticulture Sub-Laboratory, Plant Science Sub-Laboratory, and Plant Ecology Sub-Laboratory, Greenhouse of the Faculty of Agriculture, and Integrated Laboratory for Research and Testing of Universitas Gadjah Mada. Four treatment levels were tested: D0 (control or without apllication), D1 (10% concentration), D2 (20% concentration), and D3 (40% concentration). Teak leaves extract application was carried out on two different weeds, namely Cyperus rotundus L. and Chromolaena odorata L., resulting in a total of 24 experimental units within the study. Teak leaf extract was applied to Cyperus rotundus L. and Chromolaena odorata, producing 24 experimental units. Fresh teak leaves were found to contain 5.47% (w/w) gallic acid equivalent phenols. Concentrations of 10% and 20% were optimal for inhibiting the germination and early growth of Siam weed, whereas 40% was most effective for inhibiting the germination and early growth of purple nutsedge.